2017
DOI: 10.1515/cclm-2016-0543
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of thyroglobulin, calcitonin, and PTH in FNA washout fluids

Abstract: Different imaging tools, circulating endocrine markers, and fine-needle aspiration (FNA) cytology are of great importance in the diagnosis and follow-up of different thyroid and parathyroid diseases. Sometimes, however, they are conflicting or inconclusive: interestingly, measuring endocrine markers (i.e. thyroglobulin, calcitonin, parathyroid hormone) in fluids from FNA proved to be a very useful complementary diagnostic tool in such cases. The determination of endocrine markers in fluids other than serum/ pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 87 publications
(160 reference statements)
2
48
0
1
Order By: Relevance
“…A limitation related to biopsy results is that the aspirates from USguided biopsy of neck lymph nodes were not routinely sent for Tg wash-out, which has been reported to increase diagnostic accuracy when combining cytologic results with Tg wash-out. 23 Seven of the 8 lesions biopsied in the undetectable serum Tg group were lymph nodes. Additionally, 10 patients initially had neck US findings that raised the possibility of recurrence but did not undergo US-guided biopsy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A limitation related to biopsy results is that the aspirates from USguided biopsy of neck lymph nodes were not routinely sent for Tg wash-out, which has been reported to increase diagnostic accuracy when combining cytologic results with Tg wash-out. 23 Seven of the 8 lesions biopsied in the undetectable serum Tg group were lymph nodes. Additionally, 10 patients initially had neck US findings that raised the possibility of recurrence but did not undergo US-guided biopsy.…”
Section: Discussionmentioning
confidence: 96%
“…The number of patients who met inclusion criteria was limited by the lack of serum Tg measurements, no postoperative neck US examinations, and the timing of the serum Tg measurements relative to neck US examinations. A limitation related to biopsy results is that the aspirates from US‐guided biopsy of neck lymph nodes were not routinely sent for Tg wash‐out, which has been reported to increase diagnostic accuracy when combining cytologic results with Tg wash‐out . Seven of the 8 lesions biopsied in the undetectable serum Tg group were lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…So, determining a cut‐off for FNA‐PTH/serum PTH ratio is more useful rather than a cut‐off level. Trimboli et al suggested this ratio as ≥2, but there were no obvious data regarding this ratio was reported . We found that values greater than 436.5 pg/mL for FNA‐PTH washout with a sensitivity of 90.3% and specificity of 88.9% ( P < 0.01 and AUC 94.3 (87.8‐100)) and a cut‐off for FNA/serum PTH greater than 3.05 with sensitivity of 91.2% and specificity of 89% ( P = 0.02 and AUC 94.5 (88.8‐100)) which implicate parathyroid lesions.…”
Section: Discussionmentioning
confidence: 72%
“…The PTH washout procedure can be used to distinguish suspicious parathyroid lesions that have negative sestamibi scan but detected on sonographic and CT scans from negative thyroid lesions and metastatic/non-metastatic lymph nodes. [9] Although a relationship between hyperparathyroidism and well differentiated thyroid carcinoma is rare, it has been reported in numerous studies. A total of 824 primary, secondary, and tertiary hyperparathyroidism patients who underwent minimal lobectomy were evaluated in a retrospective study conducted by Burmeister et al Thyroid carcinoma was detected in 18 (2.6%) of 700 patients with PHPT, and 22 patients were found to have thyroid carcinoma among total of 824 patients.…”
Section: Discussionmentioning
confidence: 99%